Divergent functional outcomes of NLRP3 blockade downstream of multi-inflammasome activation: therapeutic implications for ALS - Clénet, Marie-Laure; Keaney, James; Gillet, Gaëlle; Valadas, Jorge S.; Langlois, Julie; Cardenas, Alvaro; Gasser, Julien; Kadiu, Irena (Frontiers in Immunology, 2023)
NOD-Like Receptor Family Pyrin Domain Containing 3 (NLRP3) inflammasome modulation has emerged as a potential therapeutic approach targeting inflammation amplified by pyroptotic innate immune cell death. In diseases characterized by non-cell autonomous neurodegeneration including amyotrophic lateral sclerosis (ALS), the activation of several inflammasomes has been reported. Since functional redundancy can exist among inflammasome pathways, here we investigate the effects of NLRP3 inhibition on NLRP3, NLR family CARD Domain Containing 4 (NLRC4) and non-canonical pathways to understand whether NLRP3 blockade alone can mitigate pro-inflammatory cytokine release and pyroptotic cell death in contexts where single or multiple inflammasome pathways independent of NLRP3 are activated. In this study we do not limit our insights into inflammasome biology by solely relying on the THP-1 monocytic line under the LPS/nigericin-mediated NLRP3 pathway activation paradigm. We assess therapeutic potential and limitations of NLRP3 inhibition in multi-inflammasome activation contexts utilizing various human cellular systems including cell lines expressing gain of function (GoF) mutations for several inflammasomes, primary human monocytes, macrophages, healthy and Amyotrophic Lateral Sclerosis (ALS) patient induced pluripotent stem cells (iPSC)-derived microglia (iMGL) stimulated for canonical and non-canonical inflammasome pathways. We demonstrate that NLRP3 inhibition can modulate the NLRC4 and non-canonical inflammasome pathways; however, these effects differ between immortalized, human primary innate immune cells, and iMGL. We extend our investigation in more complex systems characterized by activation of multiple inflammasomes such as the SOD1G93A mouse model. Through deep immune phenotyping by single-cell mass cytometry we demonstrate that acute NLRP3 inhibition does not ameliorate spinal cord inflammation in this model. Taken together, our data suggests that NLRP3 inhibition alone may not be sufficient to address dynamic and complex neuroinflammatory pathobiological mechanisms including dysregulation of multiple inflammasome pathways in neurodegenerative disease such as ALS.